2017
DOI: 10.1080/15287394.2017.1340208
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of Macondo oil and corexit on sheepshead minnow (Cyprinodon variegatus) during early development

Abstract: During the 2010 Deepwater Horizon (DWH), oil spill an estimated 800 million L oil and 7.9 million L dispersant entered the environment. The potential adverse effects of the oil-dispersant mixture are poorly understood. The aim of this study was to investigate the impacts of this mixture on early development of sheepshead minnow (Cyprinodon variegatus), a small-bodied estuarine fish commonly found in the area affected by the DWH spill. Embryos were exposed to a chemically enhanced water accommodated fraction (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Embryonic cardiac effects resulting from hydrocarbon exposure, as demonstrated in the F 1 embryos from sheepshead minnow exposed to low HEWAF in the present study, is a well‐established phenomenon in fish. It has been demonstrated that PAHs can cause altered cardiac functioning directly, in PAH‐exposed embryos (Incardona et al , , ; Bosker et al ), and indirectly, in embryos collected from PAH‐exposed parental fish (Corrales et al ; Perrichon et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic cardiac effects resulting from hydrocarbon exposure, as demonstrated in the F 1 embryos from sheepshead minnow exposed to low HEWAF in the present study, is a well‐established phenomenon in fish. It has been demonstrated that PAHs can cause altered cardiac functioning directly, in PAH‐exposed embryos (Incardona et al , , ; Bosker et al ), and indirectly, in embryos collected from PAH‐exposed parental fish (Corrales et al ; Perrichon et al ).…”
Section: Discussionmentioning
confidence: 99%